Hubungan Dukungan Sosial Pengasuh dengan Kepercayaan Diri Anak di Tempat Penitipan Anak Al-Fajril Ulum - Nadiva Adelia Akilie; Nabila Sinto; Raihan Abaidata; Ardia Regita Datunsolang (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This study seeks to examine the relationship between social support provided by caregivers and the level of self-confidence among children at the Al-Fajril Ulum daycare. Social support from caregivers, including emotional attention, positive interactions, and opportunities for children to explore their surroundings, is assumed to play a vital role in children’s psychosocial development, particularly in fostering self-confidence. The research employed a quantitative approach with a correlational design, involving caregivers and early childhood children at the Al-Fajril Ulum daycare as respondents. Data analysis revealed a strong and significant positive correlation between caregiver social support and children’s self-confidence (r = 0.76, p < 0.05). These results suggest that higher levels of social support are associated with stronger self-confidence in children. Children who receive consistent emotional support and encouragement tend to show greater confidence in social interactions and learning activities. The findings highlight the critical role of caregiver involvement and the quality of care provided in childcare institutions as a fundamental basis for supporting children’s emotional and social development during early childhood.